Włodzimierz Hagemejer and his work - Bochenek, Mirosław (Ekonomia i Prawo. Economics and Law, 2019)
Motivation: W. Hagemejer was an assistant lecturer at the Jagiellonian University in Krakow and a professor at Nicolaus Copernicus University in Toruń. He also worked in five scientific institutes. He fought during the Second World War on the African and Italian fronts. During the Stalinist period, he was unjustly detained in prison. Nevertheless, he was forgotten by economists. Aim: The aim of the article is to extract from oblivion the life and scientific achievements of W. Hagemejer. The research subject of the following considerations is an attempt at an evaluation of the originality of his works. Results: W. Hagemejer published valuable works on the elasticity of demand, the condition of the Polish economy, the structure and development trends of consumption of urban and rural households in connection with market equilibrium, inflation undermining the purchasing power of money and people’s savings, the profitability of agricultural production, economic history, and many other issues. Most of his publications are of a mathematized character and contain a wealth of statistical material. He was a supporter of quantitative methods in economics.